Chronic inflammation, cancer development and immunotherapy - Wen, Yalei; Zhu, Yingjie; Zhang, Caishi; Yang, Xiao; Gao, Yuchen; Li, Mei; Yang, Hongyan; Liu, Tongzheng; Tang, Hui (Frontiers in Pharmacology, 2022)
Chronic inflammation has been demonstrated to play a pivotal role in the tumorigenesis and tumor progression. Cancer cells interact with surrounding stromal cells and pro-inflammatory cells/Intrinsic immune cells to form the inflammatory tumor microenvironment (TME). IL-6, MIF, immune checkpoint factors and other cytokines produced by tumor-associated macrophages, myeloid-derived suppressor cells (MDSCs), neutrophils and other intrinsic immune cells in TME are the main mediators of intercellular communication in TME, which link chronic inflammation to cancer by stimulating different oncogenic signaling pathways and promoting immune escape to promote tumorigenesis and progression. In parallel, the ability of monocytes, Tregs and B regulatory cells (Bregs) to perform homeostatic tolerogenic functions is hijacked by cancer, leading to local and systemic immunosuppression. Standard treatments for advanced malignancies such as chemotherapy and radiotherapy have improved in the last decades. However, clinical outcomes of certain malignant cancers are not satisfactory due to drug resistance and side effects. Immunotherapy with immune checkpoint inhibitors is a promising approach for cancer treatment, although response rates are limited due to the immunosuppressive TME. Emerging evidence reveals that ideal therapies include elimination of tumor cells, disruption of tumor-induced immunosuppression by targeting immunosuppressive cells as well as reactivation of tumor suppressor effector T cells by checkpoint inhibitors. Here, we review the impacts of the major pro-inflammatory cells, mediators and their downstream signaling molecules in TME on tumorigenesis and progression. We also discuss the application of targeting important members of the TME and immune checkpoint therapies (ICT) in the clinical management of cancer.